2017
DOI: 10.1371/journal.pone.0175144
|View full text |Cite
|
Sign up to set email alerts
|

A novel multicopper oxidase (laccase) from cyanobacteria: Purification, characterization with potential in the decolorization of anthraquinonic dye

Abstract: A novel extracellular laccase enzyme produced from Spirulina platensis CFTRI was purified by ultrafiltration, cold acetone precipitation, anion exchange and size exclusion chromatography with 51.5% recovery and 5.8 purification fold. The purified laccase was a monomeric protein with molecular mass of ~66 kDa that was confirmed by zymogram analysis and peptide mass fingerprinting. The optimum pH and temperature of the enzyme activity was found at 3.0 and 30°C using ABTS as substrate but the enzyme was quite sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(21 citation statements)
references
References 61 publications
2
19
0
Order By: Relevance
“…The decolorization of RBBR, an anthraquinone dyes, was evaluated through the application of the purified laccase from Isolate ZUL62. We found the decolorization of RBBR was about 62% in the initial substrate concentration of 100 ppm within 24 h. Furthermore, other studies showed several results for decolorization of RBBR as follow: (i) T. versicolor U97 fungal culture was about 50% and 85% in 96 h and 144 d, respectively (Sari et al 2012b); (ii) Purified laccase of Arthrospira maxima was about 49% in 96 d (Afreen et al 2017); (iii) Purified laccase of Armaliraia sp F022 was about 70% in 48 h (Hadibarata et al 2012); (iv) purified laccase of Paraconiothyrium variabile was about 47% in 3 h by addition of laccase mediator (Forootanfar et al 2012). The increasing of RBBR concentration resulted in the reduction of decolorization (Figure 4).…”
Section: Discussionmentioning
confidence: 49%
“…The decolorization of RBBR, an anthraquinone dyes, was evaluated through the application of the purified laccase from Isolate ZUL62. We found the decolorization of RBBR was about 62% in the initial substrate concentration of 100 ppm within 24 h. Furthermore, other studies showed several results for decolorization of RBBR as follow: (i) T. versicolor U97 fungal culture was about 50% and 85% in 96 h and 144 d, respectively (Sari et al 2012b); (ii) Purified laccase of Arthrospira maxima was about 49% in 96 d (Afreen et al 2017); (iii) Purified laccase of Armaliraia sp F022 was about 70% in 48 h (Hadibarata et al 2012); (iv) purified laccase of Paraconiothyrium variabile was about 47% in 3 h by addition of laccase mediator (Forootanfar et al 2012). The increasing of RBBR concentration resulted in the reduction of decolorization (Figure 4).…”
Section: Discussionmentioning
confidence: 49%
“…Fungal laccases typically have 3 to 10 glycosylation sites, and 10 to 50% of their molecular weight is attributed to glycosylation and deglycosylation of laccase affects its enzyme kinetics [56].After SDS-PAGE electrophoresis a band excised from the gel was subjected for identification by using MALDI_TOF analysis. A band at ~ 62 kDa was digested with trypsin into 10 fragments in the range of P1 to P10 (22 to 250 amino acid sequence) ( GAA87354.1) and confirmed that the purified enzyme was laccasev [57]. Km and Vmax of purified laccase were 26.8 mM which is a good activity of the enzyme.…”
Section: Discussionmentioning
confidence: 78%
“…The isocratic chromatographic separation parameters were-detection: PDA 254 nm; mobile phase: mixture of acetonitrile 60%, water 40%, flow rate of 1 ml min À1 . The total run time was 45 min (Challouf et al 2011;Afreen et al 2017).…”
Section: Analysis Of Metabolite Profilesmentioning
confidence: 99%